-4(p+2)-p-10=-5(p+5)+7

Simple and best practice solution for -4(p+2)-p-10=-5(p+5)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(p+2)-p-10=-5(p+5)+7 equation:


Simplifying
-4(p + 2) + -1p + -10 = -5(p + 5) + 7

Reorder the terms:
-4(2 + p) + -1p + -10 = -5(p + 5) + 7
(2 * -4 + p * -4) + -1p + -10 = -5(p + 5) + 7
(-8 + -4p) + -1p + -10 = -5(p + 5) + 7

Reorder the terms:
-8 + -10 + -4p + -1p = -5(p + 5) + 7

Combine like terms: -8 + -10 = -18
-18 + -4p + -1p = -5(p + 5) + 7

Combine like terms: -4p + -1p = -5p
-18 + -5p = -5(p + 5) + 7

Reorder the terms:
-18 + -5p = -5(5 + p) + 7
-18 + -5p = (5 * -5 + p * -5) + 7
-18 + -5p = (-25 + -5p) + 7

Reorder the terms:
-18 + -5p = -25 + 7 + -5p

Combine like terms: -25 + 7 = -18
-18 + -5p = -18 + -5p

Add '18' to each side of the equation.
-18 + 18 + -5p = -18 + 18 + -5p

Combine like terms: -18 + 18 = 0
0 + -5p = -18 + 18 + -5p
-5p = -18 + 18 + -5p

Combine like terms: -18 + 18 = 0
-5p = 0 + -5p
-5p = -5p

Add '5p' to each side of the equation.
-5p + 5p = -5p + 5p

Combine like terms: -5p + 5p = 0
0 = -5p + 5p

Combine like terms: -5p + 5p = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 2(4x+1)-3(2x+3)=5 | | -25p-5(2-6p)=3(p-3)-11 | | 6(-2x+5)=-18 | | 5=12x-4.9x^2 | | -5(x+3)+2(x-1)=-14 | | 2x+-7=6+x | | 2y-5x=0 | | 191-6x=30x+23 | | N=9200ln(18) | | 15(v+4)-3v=4(3v+4)-18 | | 2(3t-5)=30-2t | | 3x^2+7x+23=0 | | 5x+21-x=7(3+x)-3x | | 21=90n | | 5x^2+7x-17=0 | | 10-10x=130-31x | | 8x+50=3x+5 | | S-5=13 | | 12x-7+5x=8(2x+1)+x-8 | | 3(k+3)-(4k-7)=-2k | | -4x-7y=21 | | 8x-14=3x+6 | | 2x+28=5x+34 | | 13=3x+1 | | 5x^4-16x^3-42x^2+5=0 | | 147000000=1.19x | | 4y-2[y-5]=2 | | 10a(3)+17a(2)+3a= | | 12y^3+60y^2+75y=0 | | 2t+t^2=4t+0.5t^2 | | 49x^2+126x+81=0 | | -2a^3-5a^2+3a^3-a^2= |

Equations solver categories